Integrated Three-Dimensional Structural and Petrophysical Modeling for Assessment of CO2 Storage Potential in Gas Reservoir - Syed Yasir Ali Shah; Jiangfeng Du; Sayed Muhammad Iqbal; Linze Du; Umair Khan; Baoyi Zhang; Jingqiang Tan (Lithosphere)
Carbon dioxide (CO2) storage in oil and gas reservoirs is one of the most effective methods for enhancing hydrocarbon recovery efficiency and mitigating climate change by securely storing CO2. However, building a realistic three-dimensional (3D) geological model for these storage reservoirs poses a significant challenge. To address this, employing a novel methodology combining 3D structural and petrophysical modeling, our study presents a pioneering effort to assess the CO2 storage potential of the faulted reservoir between the G- and E-sands of the Lower Goru Formation in the Kadanwari Gas Field (KGF), Middle Indus Basin (MIB), Pakistan. Analysis of seismic data revealed a complex reservoirs structure affected by normal faults oriented in a northwest–southeast direction. These faults partition the reservoir into several compartments and could serve as potential pathways for CO2 migration. Three-dimensional structural modeling unveiled complex features, for example horsts, grabens, and half-grabens, formed through multiple deformation stages. Petrophysical modeling indicated promising reservoir characteristics, that is high porosity and permeability in the desired zone. Three-dimensional property models were generated using sequential Gaussian simulation to represent the distribution of petrophysical properties, for example porosity, permeability, shale volume, and water saturation. Geological uncertainties were incorporated enabling the calculation of pore volume distribution and corresponding uncertainty. A novel technique was developed to assess the probable CO2 storage potential in the KGF, considering its distinctive features. The study revealed a storage potential ranging from 10.13 million tons (P10) to 101.54 million tons (P90), with an average potential of 53.58 million tons (P50). Our study offers a comprehensive approach to evaluating CO2 storage potential in complex geological zones, filling a knowledge gap in existing literature on carbon neutrality efforts in Pakistan. These findings lay the groundwork for future initiatives in geological CO2 storage in the MIB and support the country’s efforts to reduce carbon emissions.